METODE SEISMIC PORE PRESSURE UNTUK PENYEBARAN TEKANAN LUAP DI BLOK ARU, CEKUNGAN SUMATRA UTARA - Jihan Cessar H. Gurning; Agus Mochamad Ramdhan (Fakultas Ilmu dan Teknologi Kebumian (FITB), Institut Teknologi Bandung (ITB), 2017)
The North Sumatra Basin is one of the Tertiary back-arc basins which has been explored since the colonial era. The existence of overpressured zone has already been recognized. This is due to the existence of shale or claystone sequence that is capable to generate overpressure condition. Therefore, the understanding and knowledge of pore pressure and the mud weight used to counter the pressure are of paramount importance. The approach used to define pore pressure value with Eaton empirical method is generally done on wells only. In this research, determination of lateral pore pressure distribution is done with the seismic image and seismic interval velocity data. Wireline log and seismic interval velocity data are both being integrated to generate the pore pressure estimation and the distribution of overpressured zone in the North Sumatra Basin. The overpressure in this research area is caused by non-loading mechanism with the transformation of smectite into illite. The top of overpressure generally follows stratigraphic layer and sometimes it crosses the stratigraphic layer.